2017
DOI: 10.1113/jp273787
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxytocin and vasopressin neuron activity in rat hypothalamic paraventricular nucleus by relaxin‐3–RXFP3 signalling

Abstract: The paraventricular nucleus of the hypothalamus (PVN) plays an essential role in the control of food intake and energy expenditure by integrating multiple neural and humoral inputs. Recent studies have demonstrated that intracerebroventricular and intra-PVN injections of the neuropeptide relaxin-3 or selective relaxin-3 receptor (RXFP3) agonists produce robust feeding in satiated rats, but the cellular and molecular mechanisms of action associated with these orexigenic effects have not been identified. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 84 publications
10
57
0
4
Order By: Relevance
“…Subsequently, more recent electrophysiology studies in the rat have revealed a strong inhibition of magnocellular PVN neurons by RXFP3-A2 in acute PVN slices and expression of RXFP3 mRNA by both oxytocin and vasopressin immunoreactive neurons (Kania et al 2017). Although no equivalent studies in mice have been completed, our initial analysis of mRNA expression from the Allen Brain Institute atlas reveals similar expression patterns of RXFP3 and oxytocin and vasopressin mRNAs in the mouse, suggesting that these observations may be conserved between species.…”
Section: Identity Of Rxfp3 Expressing Neurons In the Pvn?mentioning
confidence: 73%
See 4 more Smart Citations
“…Subsequently, more recent electrophysiology studies in the rat have revealed a strong inhibition of magnocellular PVN neurons by RXFP3-A2 in acute PVN slices and expression of RXFP3 mRNA by both oxytocin and vasopressin immunoreactive neurons (Kania et al 2017). Although no equivalent studies in mice have been completed, our initial analysis of mRNA expression from the Allen Brain Institute atlas reveals similar expression patterns of RXFP3 and oxytocin and vasopressin mRNAs in the mouse, suggesting that these observations may be conserved between species.…”
Section: Identity Of Rxfp3 Expressing Neurons In the Pvn?mentioning
confidence: 73%
“…This is also in line with in vitro studies that reveal RXFP3 inhibits cAMP signalling (Liu et al 2003), which is more consistent with an inhibition of target neurons. Therefore, if CRH neurons expressed RXFP3, activation of this receptor would likely result in inhibition of their activity, resulting in a reduction, rather than an elevation, in HPA axis activity (see Kania et al 2017).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations